Analisis Risiko Pasar, Risiko Kredit, dan Risiko Likuiditas Terhadap Kinerja Keuangan Perusahaan: Studi Literatur Dalam Perspektif Akuntansi dan Manajemen Keuangan - Mawar Agustina; Stela Tri Yuni Purba (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the effects of market risk, credit risk, and liquidity risk on corporate financial performance from accounting and financial management perspectives. The topic is relevant because firms and banks face market volatility, default uncertainty, and short-term funding pressures that may affect profitability, cash flow, and stakeholder confidence. This study employs a literature review method by examining journal articles published between 2022 and 2025 concerning financial risk and financial performance. The novelty of the study lies in its integrated discussion of three risk categories that are commonly examined separately. The review indicates that market risk affects financial performance through changes in interest rates, exchange rates, stock prices, and commodity prices. Credit risk is associated with asset quality, non-performing loans, credit loss provisions, and borrowers’ ability to fulfill their obligations. Liquidity risk influences performance through cash availability, loan-to-deposit structure, adequacy of current assets, and the firm's ability to meet short-term liabilities. The findings also reveal that the relationship between financial risk and financial performance is not always consistent, as it depends on firm characteristics, industry sector, governance quality, and macroeconomic conditions. The study concludes that integrated risk management is essential to maintain sustainable financial performance.